Akibat Hukum Kartu Keluarga Bagi Pasangan Kawin Tidak Tercatat Menggunakan Surat Pernyataan Tanggungjawab Mutlak Berdasarkan Peraturan Menteri Dalam Negeri Nomor 108 Tahun 2019 Tentang Persyaratan dan Tata Cara Pendaftaran Penduduk dan Pencatatan Sipil - Dian Amelia; Ulfanora Ulfanora; M. Iflah Febrizal (UNES Law Review, 2023)
Marriage in society many occur without registration by the state, or known marriages have not been registered. According to The Domestic Affairs Minister Number 108 Year 2019 regarding the terms and regulations of the registration of the population and the civil record of married couples who have no record of marriage books can also record marriages in the occupational and civil record service by signing a waivement of marriage responsibilities. The purpose of this study is to find out the mechanisms and consequences of the law of issuing family cards for unregistered married couples using a letter of absolute liability based on The Domestic Affairs Minister Number 108 Year 2019. Research using normative juridical method with the nature of descriptive analysis research. The results of this study explain that violations ways to make a new family card for unregistered married couples must complete the requirements of filling the form F1.05 or A letter of absolute liability of marriage/divorce has not been registered and known by two witnesses and attaching a letter marriage has not been registered. Second, The legal result of publishing a family card for a married couple has not been recorded using a a letter of absolute liability based on Domestic affairs minister number 108 year 2019. In general, the increase in marriage practice has not been registered, Increased application for marriage books through the validation path, Increased demand for marriage confirmation, It also affects wife and children.